THE REGIONAL CENTERS OF POWER: IS THERE A CONFLICT OF INTERESTS,IDEOLOGICAL COOPERATION, OR A CONFLICT OF STRATEGIES AMONG THEM IN CENTRAL ASIA? - OMAROV, Noor; USUBALIEV, Esen (CENTRAL ASIA AND THE CAUCASUS, 2008)
The geopolitical vacuum of the post-Soviet period in Central Asia soon developed into a security vacuum to be filled, in the latter half of the 1990s, with various regional and subregional units set up by countries located outside the region. Many of them claimed regional leadership and monopoly domination in the Eurasian security system.1 In the wake of 1991, the regional countries, in turn, restored the wide contacts, within the geopolitical and geo-economic context, interrupted by their long isolation, and also revived the natural course of interaction with the adjacent regions. This made them more responsive, to a certain extent, to the influence of their neighbors, members of all sorts of security structures on the Eurasian continent. The region, a closely integrated unit of Soviet times, is now torn apart by centrifugal and centripetal forces, but there is an obvious and natural desire to restore the geopolitical unity of the past on a new basis. The newly independent Central Asian states remain dependent on the old centers of influence (Russia, China, and the Middle East), while moving at the same time toward new geopolitical partners represented by the United States and the European Union.It should be borne in mind that this process was part of the global developments and, as such, spoke of the post-Soviet Central Asian states’ intention to integrate into the global expanse and join the global struggle against transnational security threats. Their foreign policies followed the principles of multilateral cooperation and active reliance on the new allies’ potential for the simple reason that, caught in the midstream of the transformations, most of the smaller Eurasian countries with their limited resources were too weak and badly needed outside support. This was one of the most obvious manifestations of the defensive strategy of their development in the globalization context, which reduced their role to that of an outsider and part of the obedient retinue of the stronger world powers.Seen through the prism of interaction among the world and regional powers in Eurasia, the above suggests the following conclusions.Each of these powers has its own ideas about the means and methods it should apply to ensure Eurasian security based on its own long-term national interests. In our case, they can be ade-quately described as projects implemented with the use of all sorts of tools. Russia’s post-Soviet project is designed to restore its former influence in Central Asia and to use the Central Asian countries as a factor con-tributing to trimming America’s role on the world scene. Russia is obviously building a new model of relations with the local countries that will take their interests and the new reality into account. Washington’s foreign policy is shaped by a set of diverse factors; even American political ex-perts cannot agree about its future and its poten-tial impact on world development.2 The American political leadership has un-doubtedly formed its ideas about Central Eurasia’s strategic future. Washington’s neo-imperial project is designed to fill in the geopolitical vac-uum, while remaining in control by setting up a chain of political regimes along the Russian and Chinese borders that are economically and finan-cially dependent on the United States. Today, the project’s more active stage is unfolding before our eyes, the pseudo-democratic Color Revolutions being one of the strategic tools. China has opted for an assimilation project born from a combination of the contemporary worldwide realities and the domestic aims of the political elite of the country with a long historical tradition. China is using the strategy of multi-lateral and bilateral cooperation in the economic and security spheres. Even though the region is of secondary importance in the context of China’s